Disparities in Primary Care Access for Infants: Implications for Medical Home Development for Infants - Eddington, Angelica; Kunnel, Binitha; Lincoln, Alicia; Thompson, David M.; Gillaspy, Stephen R. (International Journal of Pediatrics and Child Health, 2016)
Background: Medical homes are proposed to provide a new standard of primary care that is comprehensive, family centered, and coordinated. Disparities in access to medical homes may affect healthcare outcomes among populations that include infants, children, and caregivers. This study examined disparities among pregnant mothers in a Midwestern state in the United States of America (USA) with regard to self-reported medical home access for their infants. Method: Data from the 2004-2008 Oklahoma Pregnancy Risk Assessment Monitoring System (PRAMS), a population-based survey of maternal behaviors, were analyzed. Medical home access was determined by the respondents answering a question about whether their child had a personal doctor or nurse familiar with their medical history. Results: A series of Cochran-Mantel-Haenszel Chi-Square (?2) tests revealed that medical home access differed significantly across race, marital status, education, age, income, insurance status of infant, and prenatal care transportation availability. Multiple logistic regression results showed that mothers who had education higher than a high school diploma, mothers with an annual household income of $50,000 or more and mothers whose infants had health insurance were more likely to report access to a medical home for their infant. Mothers with an annual income of less than $20,000 and no transportation were less likely to report access to a medical home. Conclusion: Similar to other disparity research, our analyses highlighted that pregnant mothers with less education, less income, mothers without insurance for their infants, and pregnant mothers without transportation reported less access to a medical home. The present study indicates a need to continue to examine implications of medical home access for pregnant mothers.